Development and feasibility testing of a new device for home-based leg heat therapy in patients with lower extremity peripheral artery disease - Bohyun Ro, MSc; John P. Spence, BBA; Paul A. Spence, MD; Christian Buckley, BS; Raghu L. Motaganahalli, MD; Bruno T. Roseguini, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
ABSTRACT: People with symptomatic lower extremity peripheral artery disease (PAD) suffer from severe leg pain, walking impairment, and reduced quality of life, but few effective treatments are available. Emerging evidence suggests that regular heat therapy (HT) may improve cardiovascular and physical function in patients with PAD. However, the lack of accessible, practical modalities for unsupervised HT, especially for elderly individuals, has hindered clinical implementation. The goals of this study were to design and assess the feasibility of a portable leg HT system for elderly patients with PAD. Building on a cryotherapy water-circulating device used in sports recovery, we developed a new prototype system consisting of a single-touch controller unit integrating a heater, water pump, and air pump, and leg sleeves with inner-layer water-circulating pads and an outer layer of inflatable bladders. The system was designed to ensure efficient heat transfer through gentle pneumatic inflation, adapting to varying limb dimensions. Safety features included temperature sensors with auto shut-off and a built-in timer. The prototype's feasibility and safety were evaluated in a single-arm pilot trial with six symptomatic patients with PAD, who were asked to apply the therapy daily for 90 minutes for 12 weeks. Primary outcomes included completion rates, safety, and device usability. Secondary outcomes were changes in blood pressure, 6-minute walk distance, calf strength, sit-to-stand performance, and quality of life. Participants underwent a 90-minute supervised treatment session with the prototype HT units to assess the acute physiological responses before starting the 12-week intervention. Leg HT gradually increased leg skin temperature from 33.8 ± 0.8°C to 38.7 ± 0.7°C at 90 minutes and reduced arterial blood pressure, with mean reductions of 13 mm Hg in systolic and 12 mm Hg in diastolic blood pressure after treatment. All participants completed the 12-week program without serious adverse events, indicating that leg HT is safe and well-tolerated. The 6-minute walk distance improved by an average of 32 m, coupled with increased calf muscle strength and reduced time for the sit-to-stand test. Improvements were also observed in self-reported walking speed and quality of life. This study represents the first step in developing a portable leg heating system for elderly patients with PAD, demonstrating that home-based leg HT is feasible and safe. However, further engineering refinements are needed to enhance portability, simplify application, and encourage long-term adherence. Developing methods to track compliance with the treatment regimen will be crucial for the success of this unsupervised, home-based therapy.